2009
DOI: 10.1016/j.apmr.2008.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Lower Thoracic Spinal Cord Stimulation to Restore Cough in Patients With Spinal Cord Injury: Results of a National Institutes of Health–Sponsored Clinical Trial. Part II: Clinical Outcomes

Abstract: Objective-To evaluate the clinical effects of spinal cord stimulation (SCS) to restore cough in subjects with cervical spinal cord injury.Design-Clinical trial assessing the clinical outcomes and side effects associated with the cough system. Setting-Out-patient hospital or residenceParticipants-Subjects (N = 9; 8 men, 1 woman) with cervical spinal cord injury Disclosure: We certify that we have affiliations with or financial involvement (eg, employment, consultancies, honoraria, stock ownership or options, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 29 publications
2
71
0
Order By: Relevance
“…These large exhaled volumes provide a standard for comparison of alternative techniques. DiMarco et al attributed their large exhaled volumes during ventral spinal cord stimulation to the spread of the electric field to stimulate the abdominal innervation at several spinal levels [5][6]18]. Lin et al also reported that stimulation of more levels with more electrodes is important [19].…”
Section: Abdominal Muscle Stimulationmentioning
confidence: 96%
See 2 more Smart Citations
“…These large exhaled volumes provide a standard for comparison of alternative techniques. DiMarco et al attributed their large exhaled volumes during ventral spinal cord stimulation to the spread of the electric field to stimulate the abdominal innervation at several spinal levels [5][6]18]. Lin et al also reported that stimulation of more levels with more electrodes is important [19].…”
Section: Abdominal Muscle Stimulationmentioning
confidence: 96%
“…In addition, clinical studies with abdominal surface electrodes and electrodes on the lower ventral side of the spinal cord have produced exhaled volumes greater than 1 L [10][11][12][13][14][15]18]. These large exhaled volumes provide a standard for comparison of alternative techniques.…”
Section: Abdominal Muscle Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another method to normalize cough flow is electrical stimulation. Di Marco et al 24 used this technique in nine cases of cervical SCI where implants were inserted between the levels T9 and L1 and demonstrated that the pressures and the flows can reach normal values. While technology allows helping patients, there are some restrictions that must be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…One important limitation of phrenic nerve stimulation to generate tidal breathing is inward movement of the paralyzed upper rib cage; however, activation of upper-thoracic, external-intercostal, inspiratory muscles can ameliorate this effect [1]. Another limitation of phrenic nerve stimulation alone is the inability to recruit abdominal muscles [5][6], which are needed to produce cough. Abdominal contractions induce high expiratory velocity and flow rates for removal of respiratory secretions and are important in management of respiratory tract infections [1].…”
Section: Introductionmentioning
confidence: 99%